2016
DOI: 10.1016/j.dss.2016.03.001
|View full text |Cite
|
Sign up to set email alerts
|

Forecasting movements of health-care stock prices based on different categories of news articles using multiple kernel learning

Abstract: -The market state changes when a new piece of information arrives. It affects decisions made by investors and is considered to be an important data source that can be used for financial forecasting. Recently information derived from news articles has become a part of financial predictive systems. The usage of news articles and their forecasting potential have been extensively researched.However, so far no attempts have been made to utilise different categories of news articles simultaneously. This paper studie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(33 citation statements)
references
References 27 publications
1
31
0
1
Order By: Relevance
“…Moreover, as already asserted, Twitter and other social platforms are prone to noise. On the other hand, web-based news data exhibit less vulnerability to noise and have recently been adopted in several prediction studies [46][47][48]. The strength of these news data is due to real-time online accessibility and rigorous professional editing.…”
Section: Related Workmentioning
confidence: 99%
“…Moreover, as already asserted, Twitter and other social platforms are prone to noise. On the other hand, web-based news data exhibit less vulnerability to noise and have recently been adopted in several prediction studies [46][47][48]. The strength of these news data is due to real-time online accessibility and rigorous professional editing.…”
Section: Related Workmentioning
confidence: 99%
“…the financial news published on non-trading day to the latest trading day. We adopt the bag-of-words model [29] to quantize the text news. First, Jieba 5 is used to realize Chinese word segmentation, and 23818 words are obtained after filtering the stop words.…”
Section: B Contrast Data Sources For Forecasting Sz50 1) Sz50 Technimentioning
confidence: 99%
“…Such studies primarily focused on classifying price direction [27], [28]. With the development of the Internet, finance related websites and applications constantly provide a large amount of textual data that increasingly affect market participants future price expectations [29]. [30] selected semantically relevant features to predict stock price movement and thus reduced the overfitting problem.…”
Section: Introductionmentioning
confidence: 99%
“…Other scholars compared artificial neural network (ANN), support vector machine (SVM) and set algorithm based on recurrent neural network and k-means clustering method to predict the price of daily Bitcoin exchange rate. In summary, it is found that the application of machine learning algorithms can significantly improve the accuracy of predictive models [19,21]. Therefore, this paper combines transaction data from multiple markets and social media data and applies a variety of machine learning methods to construct a price prediction model for cryptocurrencies.…”
Section: Introductionmentioning
confidence: 99%